TINJAUAN PERBANDINGAN KARAKTERISTIK KUAT TEKAN, KUAT LENTUR DAN INFILTRASI BETON PORUS MENGGUNAKAN AGREGAT ALAMI DENGAN AGREGAT CRUSHING - Jempater Agus Salim Sirait; Eri Setia Romadhon (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2022)
Porous concrete is a type of concrete with high porosity that is applied as a concrete slab that allows rainwater and waters from various other sources to pass through, thereby reducing waterlogging that is commonly found in conventional concrete and increasing the groundwater level. This study aims to determine the comparison of the characteristics of the compressive strength, flexural strength and infiltration speed of shaft concrete when using coarse aggregate of natural stone with comparison of coarse aggregate of crushed stone. Measurement of concrete characteristics using an experimental study method conducted at the Concrete Laboratory. The results of the data analysis obtained that the compressive strength of the shaft concrete when using natural aggregate at the age of 3 days was 7.6 Mpa, the age of 7 days was 8.6 Mpa and the age of 28 days was 15.4 Mpa; The flexural strength of the shaft concrete when using natural aggregate at the age of 7 days is 1.6 MPa and the age of 28 days is 1.9 MPa; Infiltration rate of shaft concrete when using natural aggregate at the age of 28 days is 2.66 mm/s. The compressive strength of the shaft concrete when using crushed stone aggregate at the age of 3 days is 8.6 Mpa, the age of 7 days is 12.5 Mpa and the age of 28 days is 18.8 Mpa; The flexural strength of the shaft concrete when using crushed stone aggregate at the age of 7 days is 1.8 Mpa and the age of 28 days is 2.0 Mpa; The infiltration rate of the shaft concrete when using crushed stone aggregate at the age of 28 days is 2.33 mm/s.